1998
DOI: 10.1023/a:1008839824942
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Thrombin contributes to the pathogenesis of acute myocardial infarction and reocclusion after thrombolysis. Thrombolytic therapy is known to induce a paradoxic increase in thrombin generation. Specific thrombin inhibition enhances thrombolytic therapy in experimental models. The aim of this study was to determine thrombin generation in patients with acute myocardial infarction treated with rt-PA and conjunctive therapy with the specific thrombin inhibitor, recombinant hirudin. Thrombin generation was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After FI-CL measurement, the calibration method was used to determine thrombin concentrations, and the recoveries were obtained by comparing the measured amounts to that of added human α-thrombin varied from 88.0% to 107.0%, which apparently provides the potentiality of the proposed aptasensor for thrombin detection in real clinical samples (Table S2). It was worthy to note that because the blood samples (4 and 5) employed were patient serums that might suffer from diseases known to be associated with coagulation abnormalities, some activation of the blood-clotting cascade may have occurred, thereby producing detectable levels of thrombin with the recoveries ranging from 103.3% to 110.0%.…”
Section: Resultsmentioning
confidence: 99%
“…After FI-CL measurement, the calibration method was used to determine thrombin concentrations, and the recoveries were obtained by comparing the measured amounts to that of added human α-thrombin varied from 88.0% to 107.0%, which apparently provides the potentiality of the proposed aptasensor for thrombin detection in real clinical samples (Table S2). It was worthy to note that because the blood samples (4 and 5) employed were patient serums that might suffer from diseases known to be associated with coagulation abnormalities, some activation of the blood-clotting cascade may have occurred, thereby producing detectable levels of thrombin with the recoveries ranging from 103.3% to 110.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed paradoxical rise in markers of in vivo thrombin generation after rtPA therapy [34, 35]. To our knowledge there are no studies of in vitro thrombin generation following rtPA treatment.…”
Section: Discussionmentioning
confidence: 90%